The XX brain : the groundbreaking science empowering women to maximize cognitive health and prevent Alzheimer's disease - Mosconi, Lisa (Avery, an imprint of Penguin Random House, 2020)
"The first book to address cognitive enhancement and Alzheimer's prevention specifically in women--and to frame brain health as an essential component of Women's Health"--